Ivan Baruch Kutisker in Finland: Initial encounters with Finnish antisemitism before the Great German Scandal - Swanström, André (Nordisk judaistik/Scandinavian Jewish Studies, 2017)
Ivan Baruch Kutisker was a Lithuanian Jewish businessman who became a prominent symbol of Nazi propaganda and antisemitism in the Weimar Republic. Before Kutisker came to Germany he had a brief engagement as the Finnish government representative to Soviet Russia. This article contributes to the research on Kutisker as well as to the research on antisemitism in Finland. Ivan Kutisker’s sojourn in Finland has been an unknown chapter in his life. Kutisker’s contact persons in Finland were Heikki Renvall, Kai Donner and K. N. Rantakari. The attitudes displayed by Renvall, Donner and Rantakari indicate that antisemitism was widespread among the Finnish political and military establishment. The article illustrates how antisemitism influenced the thinking and decision-making of high-ranking Finnish officials.